Assess the effectiveness of training module on knowledge and skill in basic life support (bls) among the care givers of clients - E.VARALAKSHMI, (International Journal of Pharma and Bio Sciences, 2016)
approximately 4280 out of every one lakh people die every year from SCA. Clients who suffered from cardiac arrest mostly lost their life before reaching the hospital. BLS training to the caregivers can greatly minimize the mortality rate among the clients through early and timely resuscitative measures. To assess the effectiveness of training module on BLS among the care givers of cardiac clients. Pre experimental one group pre test –post test design was used. The study was conducted in the medical cardiac unit and intensive care unit at Railway Hospital, Chennai.60 caregivers of cardiac clients, who satisfied the inclusive criteria, were selected using non-probability convenience sampling technique. A training module on knowledge and skill in BLS which contained information (lecture), education (video show), demonstration (manikin) and communication (pamphlet) module on BLS was provided. The level of knowledge was assessed by using structured questionnaire .The skill was assessed by observational check list. Descriptive and inferential statistics was used to analyze the comparison of pre and post assessment level of knowledge. It revealed that the mean improved knowledge score was 23.05 and 98.06. The calculated ‘t’ value of 41.05 was found to be highly significant at p< 0.001 level. The analysis of the post training level of skill revealed, that majority 56(93.33%) showed improved skill. The study concluded that there was a significant difference between the pre and post test level of knowledge and skill. Training module is more effective in improving the knowledge and skill in BLS among the care givers of clients. This can significantly enhance the reduction of mortality rate among cardiac clients.